Theoretical analysis of Sn-doped ZnS for optoelectronic applications. (March 2020) - Gaur, A; Khan, K; Soni, A; Dashora, A; Sahariya, J; Ahuja, U
Abstract: The wide band gap semiconductors like ZnS have gained tremendous response in the optoelectronic applications claiming their significant role in device operability at varied compositions and temperature. We have performed a detailed study of pure and Sn doped ZnS using Perdew-Burkhe-Ernzerhof (PBE) exchange correlation as embodied in Wien2k code. The doping of 6.25% Sn at Zn site, in ZnS has reduced the band gap (Eg ) to 1.70 eV from 2.15 eV (Eg for bulk ZnS) thus making it more suitable for the applications of solar cell. Various properties such as band structure, density of states and integrated absorption coefficient depicting their electronic and optical nature are examined. The spectra of absorption curve states the possibility of material to be solar if it lies in the visible spectra range of 0-5 eV.